Heat dissipation in bituminous asphalt catalyzed by different metallic oxide nanopowders. (22nd March 2021) - Qureshi, Farsan Ali; Ahmad, Naveed; Ali, Hafiz Muhammad
Highlights: Bitumen modified by the metal oxides at nanoscale enhanced heat transfer capability. Modified bitumen dissipates around 8% of heat while their asphalt mixes 14%. On discharge, modified asphalt mixtures show a steadier decline in the temperature. Abstract: The conventional bitumen, which is very sensitive to temperature, used in roads construction has very low thermal conductivity due to which heat absorbed is accumulated within it and a very less fraction of it is dissipated. Nanotechnology was introduced to overcome this issue where bitumen was modified by several metallic oxide powders at nanoscale. Nano-TiO2, nano-ZnO and nano-Al2 O3 were mixed with bitumen separately to examine their ability to enhance its property to dissipate heat. Experiments were carried out on the unmodified and modified samples of bitumen and their corresponding asphalt mixes in heat sinks to study the behavior of heat transfer. Heat sink containing sample was thermally charged for 180 min with different heat fluxes of 0.8 kW/m 2, 1.0 kW/m 2 and 1.2 kW/m 2, all at constant charging rates followed by cooling/ discharging for 120 min. Temperature curves against time for the whole charging/ discharging cycle indicated that the bitumen and asphalt, each modified with metal oxide nanopowders, showed a maximum heat dissipation of 14% to 16% as compared to unmodified samples after complete charging. Moreover, the discharging phase of the curves showed that the nano modified specimens had a steadier temperature drop than the virgin specimens endorsing the improvement in their heat dissipation property.